Efficient synthesis of α(1, 2)-linked oligomannoside derivatives through one-pot glycosylation. (August 2020) - Sano, Kanae; Ishii, Nozomi; Kosugi, Misa; Kuroiwa, Ayumi; Matsuo, Ichiro
Abstract: An α(1, 2)-linked oligomannoside derivative having a free C-2 hydroxyl group and a C-3 pivaloyl group was synthesized from a thiophenyl mannose derivative 1 using a one-pot self-condensation and applying a α-stereoselective procedure. The mannosylation exclusively generated α-mannoside linkages. The observed α-directing effect was rationalized by the remote participation of the pivaloyl group in C-3 position. The polymerization degree was controlled by the promoter amount providing the mannobiose derivative as a major product. Applying this method eliminated many synthetic steps. The α(1, 2)-linked oligomannoside derivatives, which are key intermediates for the synthesis of oligomannose type N -glycans for glycoproteins, were easily prepared. Graphical abstract: Image 1 Highlights: α(1, 2)-linked oligomannoside derivatives were synthesized using a one-pot method. The mannosylation exclusively generated α-mannoside linkages. α(1, 2)-linked mannobiose and mannotriose derivatives were also easily prepared. The α-directing effect was caused by the remote pivaloyl group in C-3 position.